(untitled) (Research, Society and Development, 2021)
Objective: To evaluate medication adherence in the population served at a Family Health Unit in a capital city in northeastern Brazil. Methods: A cross-sectional, observational, descriptive study was carried out with patients linked to family health from January 2017 to January 2019 in Salvador, Bahia, Brazil. EPI INFO software compiled data from patients’ medical records regarding the epidemiological profile and prevalent diseases. Data on medication adherence were assessed using the Morisky-Green questionnaire. The Micromedex® software was used to verify potential drug interactions. Results: The population consisted of 121 people seen at the health unit, predominantly brown women (83.6% and 46.3 respectively), with a prevalence of arterial hypertension (65.7%) and diabetes mellitus (40.3%). Only 37.3% of patients showed maximum medication adherence, mainly due to forgetfulness and carelessness when using the medication (41.8%). 37.9% of the patients stated that they had to pay financially for partial or total treatment, even with low purchasing power (77.7% with 2 minimum wages or less). Most of the prescribed drugs were related to the cardiovascular system and 20.9% of the prescriptions had potential drug interactions. Conclusion: Medication adherence was intermediate for a population with low income and average education (52.2%), with a high prevalence of diseases that affect the cardiovascular system.